Effects of CO2 flow rate in supercritical fluids extraction of polygonum minus roots - Masturah Markom; Nur Afiqah Mohd Azhari; Nurina Anuar; Ismanizan Ismail (Penerbit Universiti Kebangsaan Malaysia, 2022)
Polygonum minus (locally known as Kesum) roots has been reported to contain bioactive sesquirtepenes compound, which is β-caryophyllene. In this study, supercritical fluid extraction using carbon dioxide was employed to investigate the effects of CO2 flow rate (2 ml/min, 3ml/min and 4 ml/min) towards essential oil yield (EO) and β-caryophyllene yields from P.minus roots. The extraction pressure, temperature and time were fixed at 80 bar, 40o C and 240 min, respectively. The results showed the highest amount EO obtained at flow rate 4 ml/min with 33.3% followed by flow rate 3 ml/min and 2 ml/min were 24% and 12.4% respectively. On the other hand, the highest amount β-caryophyllene was obtained at the lowest flow rate of 2 ml/min with 7.69% yield, followed by 3ml/min (1.62%) and 4 ml/min (1.54%). It can be explained that by increasing the CO2 flow rate, it will increase the initial extraction rate and the overall extraction of EO. However, mass transfer resistance limits the amount of β-caryophyllene transported to the bulk solvents with increasing CO2 flow rate. Thus, further study is needed to overcome the mass transfer limitation and improve the overall extraction of β-caryophyllene from P.minus roots.